Assessment of Oxidative Stress and Biometric Data in a Captive Colony of Hamadryas Baboons (Papio hamadryas Linnaeus, 1758) at the Ravenna Zoo Safari (Italy) - Barbara Biancani; Monica Carosi; Michele Capasso; Giacomo Rossi; Simona Tafuri; Francesca Ciani; Chiara Cotignoli; Francesco Zinno; Elena Venturelli; Matteo Galliani; Federica Spani (Veterinary Sciences)
This study evaluates the health of a captive colony of Hamadryas baboons at Ravenna Zoo Safari (Italy), focusing on oxidative stress markers and biometric data. Forty-eight individuals were assessed during routine veterinary procedures: males underwent vasectomy, and females were checked for pregnancy. Biometric data collected included body weight, body length, and genital measurements in males, while females were evaluated for reproductive status. Oxidative stress was measured using two tests that assess both harmful pro-oxidant levels and the body’s antioxidant defenses. Results showed no significant differences in oxidative stress levels between sexes, although males and females differed in body weight. Pregnant and postpartum females exhibited higher oxidative stress, likely due to the metabolic and hormonal demands of reproduction. This supports the idea that reproductive activity increases the production of reactive oxygen species, requiring stronger antioxidant responses. In males, correlations between body weight and genital measurements suggest these could help estimate age in the absence of birth records. No link was found between oxidative stress and body weight, indicating limited age-related effects on these markers. Overall, the study highlights the importance of monitoring oxidative stress in captive primates to better understand the effects of reproduction and aging, and to improve welfare and management practices.